Recommendations for Ukraine on Introduction of Information Democracy - Митко, Антоніна Миколаївна; Mytko, Antonina M. (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The paper researches the optimization process of information democracy in Ukraine. The problems, which can be solved by information democracy include: increasing public confidence in the government, the legitimacy of the government and public understanding of power, the interests of citizens and public services, equal access to the political process, effective representation in the decision-making processes in political and administrative matters, and participation of citizens through their involvement in policy-making through public consultation and debate. The experience of implementing IT tools of democracy in Ukraine shows that through the use of Internet technology people gain new opportunities to participate in the political process, in particular, increasing their awareness on important political issues of the state and local authorities.

Artykuł bada proces optymizacji demokracji informacyjnej w Ukrainie. Wśród obszarów problemowych, które rozwiązać może demokracja informacyjna znajdują się: zwiększanie zaufania publicznego do rządu, legitymizacja rządu i społeczne zrozumienie władzy politycznej, interesów obywateli i służb publicznych, równy dostęp do procesu politycznego, skuteczna reprezentacja w procesach decyzyjnych w sprawach politycznych i administracyjnych, uczestnictwo obywateli poprzez ich zaangażowanie w tworzenie polityki przy pomocy konsultacji publicznych i debat. Doświadczenie w ustanawianiu narzędzi demokracji informacyjnej w Ukrainie pokazuje, że przez zastosowanie technologii internetowych tworzone są nowe możliwości uczestniczenia w procesie politycznym dla obywateli, a w szczególności zwiększania ich świadomości dotyczącej ważnych kwestii politycznych państwa i władz lokalnych.
Keywords: Information Democracy; Ukraine; optimization; inetrnet platform; information; power; government; opportunity; demokracja informacyjna; optymalizacja; platforma internetowa; władza; rząd; możliwości